2012
DOI: 10.5324/nje.v22i2.1561
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk factors in community-dwelling elderly people

Abstract: Falls are a common and serious problem for older adults. Approximately one-third of older communitydwelling people fall at least once a year. The main purpose of this paper is to present risk factors for fall in older people living at home. The databases used for identifying documentation of risk factors are Cinahl, Eric, ISI Web of Science, Cochrane Medline, Psycinfo and dissertation. Many psychosocial and medical conditions and impairment of sensorimotor function, balance and gait have been shown in large ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 176 publications
1
33
1
6
Order By: Relevance
“…Previous studies have found anemia related to disability [12] and physical function [3]. A recent review study [29] found a U-shaped association between physical activity and falls, where the most inactive and the most active have the highest risk of falling. This can be due to different fall contexts, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found anemia related to disability [12] and physical function [3]. A recent review study [29] found a U-shaped association between physical activity and falls, where the most inactive and the most active have the highest risk of falling. This can be due to different fall contexts, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that physical activity is critical to fall prevention; there seems to be a U-shaped relationship. Specifically, the risk for falls is reduced among physically active people, but there is an increased risk among the most active and inactive individuals (Bergland, 2012;Moayyeri, 2008;Stenhagen, Ekström, Nordell, & Elmståhl, 2014). Furthermore, despite repeatedly demonstrating that engaging residents in function and physical activity does not increase the risk of falls Gruber-Baldini, Resnick, Hebel, Galik, & Zimmerman, 2011), staff, families, and residents continue to believe that any activity will result in a fall.…”
Section: Nursing Home Settingsmentioning
confidence: 97%
“…3,4 Such functional decreases related to balance control due to aging accelerate risk of falling while conducting activities that generate temporary postural instability such as gait. 5,6 Generally, balance control ability is clinically evaluated with tools that estimate task performance ability to perceive and predict risk of falling. These tools are widely used since performance ability can be simply quantificated through duration, velocity, distance, etcetera in task performance.…”
Section: Introductionmentioning
confidence: 99%